AN OVERVIEW OF BIG-DATA AND CLOUD COMPUTING (International Journal of Engineering and Computer Science, 2014)
Big data and Cloud computing both are most popular topics of recent days for organizations across the globe. Big data is a rapidly expanding research area spanning the fields of computer science, information management and it has become a ubiquitous term in understanding and solving complex problems in different disciplinary fields such as engineering, applied mathematics, medicine, computational biology, healthcare, social networks, finance, business, education, transportation and telecommunications. Cloud computing is a service delivered over the internet for computation, data accessing & storage by creating scalability, flexibility and minimum cost. It is a next generation platform for computation which offers various services and applications to the user without physically acquiring them